Tingkat Motivasi Petani dalam Usahatani Padi Organik di Kabupaten Karanganyar melalui Pendekatan Teori Hierarki Kebutuhan Maslow - Indah Nurhidayati; Agustono; Refa’ul Khairiyakh; Amalia Nadifta Ulfa (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
Food is the second pillar of the Sustainable Development Goals (SDGs). Currently, food challenges are evolving from mere production quantity issues to product quality issues. Rising public awareness of food safety is driving the popularity of organic markets, with organic rice a key commodity based on market demand in Indonesia. This study analyzes the motivation levels of farmers in Karanganyar Regency in implementing organic farming systems through the perspective of Maslow's Hierarchy of Needs Theory. Research findings reveal that farmer motivation is high across all levels of need. The need for love is the primary driver, with the highest score (3.93), underscoring the importance of relationships between farmers. Although farmers' perceptions of organic farming systems are very positive, an anomaly has been observed in the form of a decline in the number of farmers in the field. The primary cause is demographic factors, with the majority of farmers being pre-elderly and elderly. This situation threatens food sustainability, necessitating regeneration measures and more accurate farmer data improvements to maintain national food stability.